2009
DOI: 10.1111/j.1468-1293.2008.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of glomerular filtration rate estimates vs. 24‐h creatinine clearance in HIV‐positive patients

Abstract: BackgroundGuidelines for kidney function monitoring and antiretroviral drug dosing are available and respectively refer to glomerular filtration rate and creatinine clearance (CrCl). ObjectiveThe aim of the study was to compare kidney function estimates vs. measured 24-h CrCl in HIVinfected subjects. MethodsA cross-sectional design was used, with comparison of Cockcroft-Gault (CG), original and simplified modification of diet in renal disease (MDRD) equations vs. measured 24-h CrCl. Subjects were HIVinfected, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
1
10
0
2
Order By: Relevance
“…In the United States HIV cohort, some discrepancies have been shown between Cockroft-Gault and MDRD, but no gold standard was applied to the population (38). In a recent Italian study, Cockroft-Gault and MDRD estimates (versus gold standard) showed a satisfactory correlation (36). Plasmatic and urinary cystatin C can be measured routinely and provide good information on serum creatinine clearance using the CKD-EPI estimation, as well as on tubular dysfunction using the serum/urinary ratio (39).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the United States HIV cohort, some discrepancies have been shown between Cockroft-Gault and MDRD, but no gold standard was applied to the population (38). In a recent Italian study, Cockroft-Gault and MDRD estimates (versus gold standard) showed a satisfactory correlation (36). Plasmatic and urinary cystatin C can be measured routinely and provide good information on serum creatinine clearance using the CKD-EPI estimation, as well as on tubular dysfunction using the serum/urinary ratio (39).…”
Section: Discussionmentioning
confidence: 96%
“…The eGFR is widely considered to be a direct measure of kidney function and reduces before the onset of symptoms of kidney failure (34,35). We chose to use MDRD evaluation of GFR because it has been previously shown to have a level of precision and accuracy sufficient for clinical decision making (36,37). All methods of GFR estimation have been discussed and compared in some studies with gold standard methods of creatinine clearance measurements.…”
Section: Discussionmentioning
confidence: 99%
“…A primeira fórmula tem sido usada desde 1976 e é a mais cotada na adequação de doses de antirretrovirais, de acordo com a maioria das diretrizes vigentes. A equação MDRD foi elaborada em 1999 e, posteriormente, simplificada em uma versão que tem sido recomendada como a mais fiel preditora da função renal, especialmente nos casos em que a mesma está reduzida em relação aos níveis normais 18 . Ela foi usada como variável preditiva da função renal.…”
Section: Métodos Resultadosunclassified
“…O padrão ouro para determinação da proteinúria e mesmo da filtração glomerular, a coleta de urina de 24h, é considerado um método de difícil aplicabilidade no conjunto de pacientes na prática clínica, razão pela qual, diversos autores têm recomendado a utilização de fórmulas para estimar a função renal. Privilegiamos o uso da MDRD simplificada, por esta ter se mostrado com maior precisão em pacientes com algum déficit de função renal 18 . A importância de rastrear a alteração precoce da função renal se destaca…”
Section: Considerações éTicasunclassified
“…There was a study reporting that the C-G and 4-variable MDRD eGFR were highly correlated, but both underestimated the 24-hour urine CrCl in HIV-infected adults without chronic kidney disease. 30 However, in some reports, the MDRD formula is considered to be more accurate than the C-G formula, which may overestimate renal function. 21,31 Using MDRD formula may still have a high level of bias, depending on creatinine assay calibration, and low precision, with approximately 80% of eGFR in the range of 70% to 130% of the measured GFR value.…”
Section: Discussionmentioning
confidence: 99%